CONTENTAL CHARACTERISTICS AND TRENDS OF THE REGIONAL ENERGY MARKET DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. This article explores the state of electricity in Ukraine, finds significant energy dependence of Ukraine on external suppliers in contradiction to existing and potential production of own energy resources, clarifies the rules and rules of energy security, describes the energy system of Ukraine, outlines the relationship between the subjects of this system in direction of monitoring the existing models of the electricity market of Ukraine. The analysis of losses and gains from the regulatory impact of the electricity market during 2014-2018, shows that the European scenario of reforming the electricity markets is the most adapted to current conditions of reality. The directions of the national policy on the electricity market in the coming years have been systematized and proposed.Тhe purpose of the article. The purpose of the article is to investigate the content, the essence, the integrity of the electricity market, given the tendency of its improvement. The important tasks are the following: generalization and refinement of the electricity market of Ukraine and the region; improvement of the existing models of functioning of the electric power industry with their further specification regarding adaptation to external changes; the circumstances for the more efficient functioning of the region's electricity market have been clarified; to propose priority directions of the national electricity market policy for the next few years.Results. Рrolonged energy efficiency program to ensure dependence on imported electricity supplies, optimize conditions for energy efficiency in transportation, and distribute energy resources to energy-efficient use by consumers. A number of legislative acts and agreements aimed at approving European standards for norms have been ratified to ensure a competitive and liberalized sector. These include, in particular, the Law of Ukraine «On the Gas Market», the Law of Ukraine «On Amendments to the Legislative Acts of Ukraine on Increasing the Transparency of Extractive Industries in Ukraine», «On National Energy Efficiency Responsibilities for 2020».Conclusiоn. During 2014-2018 in the electricity market of Ukraine there were both losses and gains: Ukraine's energy dependency has been the impetus for diversifying supply sources to reduce dependency. In this direction, the agreement on the construction of power units in Khmelnitsky AU was terminated, an agreement was signed for the supply of nuclear fuel batches with the American company Westinghouse Clectric Company at Ukrainian power plants, an agreement was concluded between SE NNEGC «Energoatom» and the international supply company YCO 12REN which can be used to produce nuclear fuel for the Ukrainian nuclear power plant at a company in Switzerland, built at the Chernobyl Exclusion Zone according to US Centralized Storage Technology for spent nuclear fuel
Keywords: electricity market, energy resources, competitiveness, profitability, monopsony, perfect competition, energy blocks